The Role of Satellite Glial Cells, Astrocytes, and Microglia in Oxaliplatin-Induced Neuropathic Pain - Ji Hwan Lee; Woojin Kim (Biomedicines, 2020)
Oxaliplatin is a third-generation platinum-based chemotherapeutic drug. Although its efficacy against colorectal cancer is well known, peripheral neuropathy that develops during and after infusion of the agents could decrease the quality of life of the patients. Various pathways have been reported to be the cause of the oxaliplatin-induced paresthesia and dysesthesia; however, its mechanism of action has not been fully understood yet. In recent years, researchers have investigated the function of glia in pain, and demonstrated that glia in the peripheral and central nervous system could play a critical role in the development and maintenance of neuropathic pain. These results suggest that targeting the glia may be an effective therapeutic option. In the past ten years, 20 more papers focused on the role of glia in oxaliplatin-induced thermal and mechanical hypersensitivity. However, to date no review has been written to summarize and discuss their results. Thus, in this study, by reviewing 23 studies that conducted in vivo experiments in rodents, the change of satellite glial cells, astrocytes, and microglia activation in the dorsal root ganglia, spinal cord, and the brain of oxaliplatin-induced neuropathic pain animals is discussed.